Preparation of special rubber material for tire - Syamsu Yoharmus; Darussamin Asril; Suparto Dadang (Proceedings : Indonesian Rubber Conference and IRRDB symposiun 2000 Indonesian Rubber Research Institute, Bogor, Indonesia, 12-14 September 2000.V.II.pp.287-298.)
At winter season automotive vehicles need tires, which have better sliding friction and grip due to ice and snow. Recent laboratory work has shown that the presence of naturally occurring nitrogenous material like protein gives positive contribution on several physical properties of rubber goods, including grip and ice traction. It establishes a chance to prepare natural rubber with higher-than normal levels of nitrogenous material to provide winter tire treads with improved grip and traction on snow and ice. An experiment to study influence of increasing of nitrogenous material content in rubber to the technical and physical properties and vulcanization characteristics was carried out at Mambang Muda crumb rubber factory, PTPN III. Such raw rubber was produced according to crumb rubber processing practices, meanwhile method for increasing nitrogen content was by incorporation of well-prepared raw skim rubber derived from naturally coagulated fresh skin latex. Physical properties measurements of vulcanisate were conducted at Bogor Research Station for Rubber Technology. The result shows that good technical properties of raw rubber produced are retained, especially those passing crepematuration period prior to crumbling and drying. Cure times become shorter, while scorch times increase with the nitrogen content of rubber. Vulcanisate properties are a bit influenced especially flax crackiing and resilience by the increase on nitrogen content in raw rubber.
Keywords: Rubber material; Tire